Study on Individual PAHs Content in Ultrafine Particles from Solid Fractions of Diesel and Biodiesel Exhaust Fumes - Małgorzata Szewczyńska; Małgorzata Pośniak; Elżbieta Dobrzyńska (Journal of Chemistry)
In order to characterize PAHs emissions of diesel engine fuelled with diesel and its blend (B20, B40). In the particle phase, PAHs in engine exhausts were collected by fiberglass filters using Electrical Low Pressure Impactor (ELPI) and then determined by a high performance liquid chromatography with a fluorimetric detector (HPLC-FL). The main content in exhaust gases from diesel engine, regardless the type of applied fuel, is constituted by the particles fraction of diameter <0.25 μm. Particles sized <0.25 μm constituted on average approximately 68% of particles in diesel exhaust gases and approx. 50% of particles emitted by biodiesel B20 and B40. When the B100 bioester additive was applied, the total emission of particles was reduced thus the volume of toxic substances adsorbed on them was lower. The analysis of chemical composition of <0.25 μm exhaust gas fraction showed that there were mainly 3- and 4-ring aromatic hydrocarbons in the exhaust gas of diesel fuel while in B40 single PAHs with the number of rings of 4 and 5 were detected. An application of ELPI permitted a further separation of <0.25 μm particle’s fraction and a real-time determination of interalia number, mass, and surface concentrations.